Representasi Sosok Ayah dalam Lirik Lagu Mendarah oleh Nadin Amizah: Analisis Teori Ferdinand de Saussure - Deby Afrizal; Anis Endang SM; Dilmai Putra (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This research is titled "Representation of the Father Figure in the Lyrics of the Song Mendarah by Nadin Amizah: An Analysis Using Ferdinand de Saussure’s Theory". The aim of this study is to analyze how the father figure is represented in the lyrics of Mendarah through Ferdinand de Saussure’s semiotic theory, focusing on the relationship between signifiers and signifieds. Nadin Amizah's song Mendarah was chosen due to its rich lyrics full of symbols and metaphors, depicting the emotional relationship between a father and child who are separated. This research uses a descriptive qualitative method with a semiotic analysis approach, identifying words, phrases, and stanzas in the lyrics as signifiers that form meanings or signifieds. The results show that although the word "father" is not explicitly mentioned, the father figure is symbolically represented through signifiers such as "a separated soul," "my heart has long been broken," "different homes," and "bleeding into." These signifiers reveal meanings related to emotional separation, internal wounds, and biological attachment that remain despite physical distance. This study demonstrates that the lyrics of Mendarah function as a symbolic communication medium, depicting a personal experience of the father-child relationship and illustrating the complexity of emotions related to family bonds.